If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 0.5((4x + -10) + (3x + 8)) Reorder the terms: 13 = 0.5((-10 + 4x) + (3x + 8)) Remove parenthesis around (-10 + 4x) 13 = 0.5(-10 + 4x + (3x + 8)) Reorder the terms: 13 = 0.5(-10 + 4x + (8 + 3x)) Remove parenthesis around (8 + 3x) 13 = 0.5(-10 + 4x + 8 + 3x) Reorder the terms: 13 = 0.5(-10 + 8 + 4x + 3x) Combine like terms: -10 + 8 = -2 13 = 0.5(-2 + 4x + 3x) Combine like terms: 4x + 3x = 7x 13 = 0.5(-2 + 7x) 13 = (-2 * 0.5 + 7x * 0.5) 13 = (-1 + 3.5x) Solving 13 = -1 + 3.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5x' to each side of the equation. 13 + -3.5x = -1 + 3.5x + -3.5x Combine like terms: 3.5x + -3.5x = 0.0 13 + -3.5x = -1 + 0.0 13 + -3.5x = -1 Add '-13' to each side of the equation. 13 + -13 + -3.5x = -1 + -13 Combine like terms: 13 + -13 = 0 0 + -3.5x = -1 + -13 -3.5x = -1 + -13 Combine like terms: -1 + -13 = -14 -3.5x = -14 Divide each side by '-3.5'. x = 4 Simplifying x = 4
| 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 | | 1/2*(3/5((2^3)-6))+1/5 | | 7/5x^2-7/9x-4/3x | | 1/2*3/5((2^3)-6)+1/5 | | 82x+4x=68.5 | | 5y+1/9=6y+5/9 | | 0.50x+0.05(80)=0.25(64) | | -8(x+5)+3=-37 | | 5x/14-3x/14-11x/14= | | -3x+2y+z=4 | | (3x+2)(5x-1)= | | (x-74)/x=0.4 | | m^4+4m^2+1=0 | | 0.08-0.01(x+2)=-0.02(3-x) | | 99=.5h+11 | | 6(y-1)/5=-2y | | 5x-2=5(x-4) | | 10x^2+3x+m=0 | | -3+6=x-10 | | x+x+x+3x=48 | | x^2+y^2=80 | | 3/7x+4/7=-8/7 | | x+x+x+6x=27 | | 2.5y+4=2y-1 | | 9(y+10)+y=2(y+3)-5 | | .4x+.8= | | -7z+3z=8z-3-z | | 2-8/2(x-1)^2+15 |